PERAN PERBANKAN DALAM PEMBIAYAAN UMKM DI PROVINSI DIY - Y. Sri Susilo (Jurnal Keuangan dan Perbankan, 2010)
This article aimed to identify and analyze the role of banks in financing small and medium business in theProvince of Yogyakarta special regency (DIY). The location researched included Kulon Progo regency,Sleman regency, Bantul regency, Gunungkidul regency, and Yogyakarta city. The samples were 220 businessmencategorized as small and medium business. Analysis tool used was descriptive approach. The result ofthis research was the role of banks in the development of small and medium business in the province of DIYwas very important. This was because the role of non-bank credit and financial institutions in the financingof small and medium business was still relatively low. The contribution of banks, particularly in supportingfinance was when small and medium business entered business development. When obtaining a bank loan,small and medium business categorized as potential, feasible, and bankable, did not usually meet difficulties.On the other hand, the potential small and medium business categorized feasible but not bankable andcategorized not feasible but bankable facilitated access to bank financing requiring a variety of supportprograms from government and also Bank Indonesia. Further, for potential small and medium business butnot feasible and not bankable the financial support was not through banks but through the revolving fundprograms and social assistance funds.